Experimental determination of conditional clearances for cylinder piston seals of compressor units - S. S. Busarov; I. S. Busarov; D. S. Titov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The current problem of determining the dependence of the conditional clearance in the cylinder-piston seal on the operating pressure at a fixed piston is solved by the authors in this paper. The experimental studies have allowed to obtain the dependence of the conditional clearances on the pressure in the cylinder-piston seal of slow-speed long-stroke units with static purge. The data obtained made it possible to determine the best seal for piston low-speed long-stroke units. In the future, the results of research will allow to modernize the existing method of calculation of working processes of low-speed long-stroke units